Disaster planning and preparedness in the hotel industry - Albattat, Ahmad Rasmi; Mat Som, Ahmad Puad (Emerald Publishing Limited, 2019)
By identifying major emergencies that have occurred in the hotel industry; investigating hotels' preparation for emergencies in the past; and exploring how hotels manage and overcome such emergencies; this book will increase the awareness of emergency managers on how to manage and overcome the impact of emergencies in the hospitality industry.
Prelims -- Introduction -- Disaster and emergency planning and preparedness in hotels -- Analysis and findings -- Conclusion and future direction -- References -- Index.
Includes bibliographical references and index.
Print version record
Keywords: Emergency management; Hospitality industry; Social Science -- Disasters & Disaster Relief; Social welfare & social services